Efforts To Improve Math Learning Outcomes About Division Of Integers Through The Stad Learning Model In Class IV SD Negeri I Dorang - Fitriyah, Eny (Social, Humanities, and Educational Studies (SHES): Conference Series, 2022)
The aims of this research is to improve the result of the students learning in multiplication and devision of integers.This research of the method using the classroom action with two cycle and place of the research in the four grade with the 32 students consist of 14 male students and 18 famale students semester 1 in acdemic years 2021/2022. The research using the instrument classrom action with using the observation sheet on the Students active, with the writing tes. The result of the research show that the result of the students in learning stated that the success and learning objective are achievement. It is known from the result of the second scyle with four meetings to improve the result of the study reach the average 6,31 in sycle I, crease to 8,5 on the cycle II individual and classical achieve to 43,75% on the cycle I, crease to 84,36% on cycle II, both the individual and classical    have  achievement  completeness  in  learning.  Therefore  can  be  conclude  thatthe  types  cooperative learning  model  STAD  can  improve  the  result  of  the  study  mathematics  about  multiplication  and  division  of integers at the four grade Elementary school in SDN 1 Dorang. As well as to the teacher is recommended to be more  the  learning development    in  the  classroom,  make  it  more  be  fun  and  the  students  are  be  active  in learning